Validity of the recovery-stress questionnaire - Tibbert, S.; Morris, T.; Andersen, M. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. I, 2008)
Introduction: Coaches and athletes have long sought the optimum level of training and the most effective ways to handle the demands of repeated competitive performances. A substantial proportion of elite athletes (around 40%) report overtraining (Kenta et al., 2001), Gould et al. (1999) reported that athletes interviewed from four US Olympic teams frequently cited overtraining as a cause of failure. Recently, researchers have shifted the conceptualisation of training and competition demands from overtraining, which focused on physical, psychological, and performance decrements resulting from training too hard, to stress-recovery imbalance (SRI), which acknowledges that appropriate recovery can moderate the impact of heavy training. To measure SRI, Kellman and Kallus (2001) developed the Recovery-Stress Questionnaire for Athletes (RESTQ-SPORT). This instrument measures general stress, general recovery, sport-specific stress, and sport-specific recovery. The RESTQ-SPORT has been through standard psychometric validation, but there are few independent tests of its construct validity. The aim of this study was to examine the construct validity of the RESTQ-SPORT by comparing scores of elite athletes in a period of intensive training and competition (HI-INT), with their scores during a less intensive phase (LO-INT). We predicted means for stress subscales would be significantly lower and means for recovery subscales would be significantly higher for the LO-INT than for the HI-INT occasion. Methods Participants were 28 male professional footballers regularly playing at the highest level in the Australian Football League (AFL). They were aged 18 to 34. The RESTQ-SPORT is a 52-item questionnaire that measures general stress (7 Subscales), general recovery (5 Subscales), sport-specific stress (3 Subscales), and sport-specific recovery (4 Subscales). Responses are made on a 7-point Likert scale from 0 (never) to 6 (always). Following ethics approval and standard consent procedures, footballers completed the RESTQ-SPORT before training four days after a league match (RESTQSPORT1) and before training, four weeks later; in the only week of a 22-week season when they had not played a league match the previous weekend (RESTQ-SPORT2). To examine the construct validity of the RESTQ-SPORT, we performed a paired t-test comparing each subscale on the HI-INT and LOINT occasions of testing. Results Means for all stress and recovery subscales moved in predicted directions. Results are presented in Table 1.